Conjugation of Anti-EpCAM Antibody on Alginate–RIP MJ-30 Nanoparticle through Carbodiimide Reaction as a Model of Targeted Protein Therapy - Ismail, Hilda; Ciptasari, Ummi H.; Ikhsan, M Arief Nur; Suryani, Fidya; Sismindari, Sismindari; Martien, Ronny; Yuswanto, Ag (Indonesian Journal of Pharmacy, 2019)
Ribosome inactivating proteins from Mirabilis jalapa L. (RIP MJ) has shown higher cytotoxic activity when being formulated as a nanoparticle. However, the selectivity of the delivery system is also an important aspect when it comes to cytotoxic cell therapy. Epithelial cell adhesion molecule (EpCAM) is a monomeric glycoprotein which is overexpressed in epithelial cancer cells. This study aim was to develop a model of targeted protein delivery system by formulating the base fraction of RIP MJ (RIP MJ-30) into alginate nanoparticles and conjugating it with anti-EpCAM antibody. RIP MJ-30 was formulated in to nanoparticle using alginate and CaCl2 as cross-linker. Optimization of conjugation reaction condition was done in the pH variation of 4.5, 5.5, and 6.5. The success of conjugation was analyzed qualitatively using native polyacrylamide gel electrophoresis (native-PAGE) method and BCA assay. The optimum formula of RIP MJ-30 nanoparticles was produced using 0.3% alginate and 0.2% CaCl2. Results indicated that optimum conjugation reaction was carried out at pH level of 5.5. The optimum native-PAGE condition was by using 8% polyacrylamide gel in duration of 6h. Characterization of nanoparticle resulted in particle size of 205.0nm, zeta potential of -6.9mV, entrapment efficiency of 71.11±4.84%, and conjugation efficiency of 89.55±6.18%. It was concluded that RIP MJ-30 was successfully formulated into alginate nanoparticle and conjugated to anti-EpCAM antibody through carbodiimide reaction using 1-ethyl-(dimethylprophilamine) carbodiimide (EDAC).